ARAH PERDAMAIAN KONFLIK PALESTINA-ISRAEL PASCASERANGAN 7 OKTOBER 2023 - Mudore, Syarif Bahaudin (Universitas Khairun, 2024)
The Palestine-Israel conflict is one of the most complex and prolonged disputes in modern history, rooted in historical, political, religious, and social factors. This paper explores the origins of the conflict, tracing its development from the Ottoman era to the establishment of the State of Israel in 1948, a pivotal turning point in the escalation of tensions. It also examines various peace efforts, such as the Camp David Accords and the Oslo Accords, highlighting the causes of their failures, including the lack of equality in negotiations and the influence of global political interests. Following the events of October 7, 2023, the paper underscores the urgency of formulating a new peace strategy that is inclusive and equitable. It identifies key points for achieving peace, such as recognizing the fundamental rights of the Palestinian people, halting Israel's colonial activities, and garnering international support for a two-state solution. Through this analysis, the paper aims to offer fresh perspectives on pathways to peace that can lead to tangible change in the region.